Ecosystem services generated by Neotropical freshwater fishes - Pelicice, Fernando M. (2022)
To understand how Neotropical freshwater fishes (NFF) benefit society, we conducted a broad literature survey to (i) map and list the ecosystem services (ES) generated by these organisms, and (ii) investigate how human activities have affected the ecosystem service chain. We found sound evidence that NFF contribute directly and indirectly to the generation of several provisioning, regulating, supporting, and cultural services. Provisioning services have been widely recognized, especially those related to fisheries, but this class also included ornamental fish, genetic pools, medicines, aquaculture, and bioindicators. Other services remain less understood and largely ignored by society. Regulating services included seed dispersal, decomposition, and top-down control, while supporting services included nutrient cycling, habitat quality, and ecosystem engineering. Cultural services associated with NFF included recreational fishing, tourism, fishkeeping, education, production of scientific knowledge, in addition to values linked to traditional communities, such as local knowledge, cosmology, and existential foundations. Human activities have negatively impacted the generation of ES, especially those related to fishing and food provisioning. This review indicates that Neotropical fishes benefit society in multiple ways, but it is imperative to improve our understanding about those benefits, and to increase conservation efforts directed to this important component of global biodiversity.